Optimization of Media Bed Height for Simple Filtration Treatment of Laundry Wastewater - Muhammad Al Kholif; Afifian Mohamad Mahrus (Environmental Pollution Journal, 2026)
Household and commercial laundry businesses contribute to water pollution by generating liquid waste with high concentrations of Biological oxygen demand (BOD), Chemical oxygen demand (COD), surfactants, and phosphates. This study aims to analyze the effect of varying the height of a combined filtration medium comprising coconut fiber, zeolite, activated carbon, and gravel on the reduction of BOD and COD levels in laundry wastewater in Bratang Perintis Street, Wonokromo District, Surabaya City. Wastewater samples were collected in 30-liter volumes, with initial BOD and COD concentrations of 320 mg/L and 718 mg/L, respectively, exceeding the quality standards set by East Java Governor Regulation No. 72 of 2013. The wastewater was gravity-fed through four 4-inch-diameter acrylic reactors with media bed heights of 8, 10, 12, and 14 cm, each operated at a flow rate of 1 L/h with two treatment cycles. The results showed a maximum BOD reduction efficiency of 53.75% and a maximum COD reduction efficiency of 55.43% in the reactor with an 8 cm media height. Reactors with thicker media did not demonstrate higher efficiency, indicating the influence of hydraulic factors on system performance. The BOD and COD levels of the effluent from all reactors still exceeded quality standards, necessitating integration with advanced treatment processes to meet discharge standards for water bodies,